Evaluation of Aerobic Exercise Induced Metabolic Stress on Serum Asprosin Levels: Comparison of Fitness Status - Algul, Sermin; Deniz, Gulnihal; Alp, Hamit Hakan; Uğraş, Seda; Ozcelik, Oguz (Progress in Nutrition, 2022)
We comparatively evaluated effects of aerobic exercise performed morning and afternoon on asprosin levels in young trained, sedentary males. A total of fifty male subjects (trained n=25, sedentary n=25) participated in morning and afternoon aerobic running exercises to approximately 70% of the subject’s maximal heart rate for about 45 min. Pre- and post-exercise venous blood samples were taken and analysed for asprosin using ELISA. Serum CK and MDA levels were determined by measuring with an autoanalysers and a HPLC, respectively. Asprosin, CK and MDA levels increased significantly at the end of both morning (p